PENGARUH CUSTOMER REVIEW, CUSTOMER RATING, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA PLATFORM SHOPEE: (Studi Kasus Pada Pengguna Platform Shopee di Institut Agama Islam Tasikmalaya Tahun 2024) - Wilda Nurafifah; Rini Muflihah (LPPM IAIT, 2024)
Information and communication technology that is developing very rapidly in the current digital era is marked by the emergence of the internet network. One aspect that is significantly influenced by technology is marketing strategy. Companies or shops sell products directly by providing a place for customers to come and buy goods. Unlike before, now there are many businesses or shops that recognize technological advances, so they use e-commerce as a marketing strategy to sell their products. In this case, reviews (customer reviews), ratings and prices have an important role in it. This study aims to determine whether there is an influence of customer reviews, customer ratings and prices on purchasing decisions on the Shopee platform for student users of the Shopee platform at the Tasikmalaya Islamic Institute in 2024. This study is a quantitative study, the type of data used is primary data where the sample taken was 116 respondents by distributing questionnaires (questionnaires). The results of the study showed that these three variables have a significant effect in a positive direction on purchasing decisions. Customer reviews, customer ratings and prices can increase sales for sellers in e-commerce and can increase customer satisfaction.